Coastal Communities Perception through Stunfish (Stunting Prevention through Fish Divercification) In Stunting Prevention Efforts - Hardianty Askar; Arwita Irawati; Wafiq Azizah (Jurnal Perikanan dan Kelautan, 2024)
This study aims to analyze the perception of coastal communities through STUNFISH (Stunting Prevention through Fish Divercification) in an effort to prevent stunting. This study is a survey research using a quantitative descriptive approach using questionnaire aids. The research was conducted in the coastal area of Sangkarrang District on Barang Lompo Island, Barang Caddi Island, and Kodingareng Lompo Island. The sampling method used the slovin formula in three conditions of coastal communities, namely toddler mothers, pregnant women, and breastfeeding mothers. The population in this study was 1,185 from three conditions of coastal communities and the number of samples was 201 respondents obtained from the calculation of the slovin formula with the number of mothers under five as many as 89 respondents, pregnant women as many as 74 respondents, and breastfeeding mothers as many as 38 respondents.  The data analysis used in the social study used Likert scale analysis with four measurement scales on the perception of coastal communities. The results showed that the perception of the level of knowledge of parents in the breastfeeding mother group had the highest presentation on the indicator of lack of knowledge at 59.46%. The perception of obstacles to stunting prevention in coastal communities in the condition of Mrs. Ballita has a poor percentage of 42.70% indicators. The perception of the level of knowledge of fishery products in the group of mothers under five had the highest percentage level in mothers under five, namely 59.55% on the indicator of knowing very well. Finally, the perception of the role of processed fishery products in stunting prevention in coastal communities was the highest percentage of 66.22% in the condition of breastfeeding mothers who thought it was very good. : Diversification, Coastal Communities, Perception, Likert Scale, STUNFISH